Kirchenaustritte seit 2018: Wege und Anlässe Ergebnisse einer bundesweiten Repräsentativbefragung - Ahrens, Petra-Angela (SI-Studien aktuell, 2022)
Petra-Angela Ahrens' study examines the reasons for and occasions and paths to leaving both the Protestant and Catholic churches. In a nationwide quantitative study, a total of 1,500 former Protestant and Catholic church members were interviewed about their leaving the church. The study was designed against the backdrop of both the peak in the wave of people deciding to leave the church in 2019 and subsequent assumptions about the significance of specific reasons for them deciding to leave. The interviewees were asked about how their relationship with the church and faith or religion had evolved during different stages of their lives. It turns out that only rarely did a concrete occasion justify their decision to leave the church, but that their alienation from the church resembles a process.